The Values of Nationalism Education in the Songs Yalal Wathon and Sang Surya: August Comte's Perspective - Nuhla Hilwa Tsabatiyya; Sofa Muthohar; Arsan Sanie (Journal of Islamic Education Thought and Development, 2025)
This study aims to analyze the values ​​of education nationalism contained in two Indonesian struggle songs, namely Yalal Wathon and Sang Surya, through the perspective of August Comte's philosophy, especially the theory of Positivism. The research method uses a qualitative approach with a literature study method. The findings of this study indicate that the lyrics of the song reflect three stages of human thought development according to Comte, namely the theological, metaphysical, and positive stages. This study found that Yalal Wathon emphasizes the emotional religious aspect (theological stage), while Sang Surya tends to emphasize rationality and scientific optimism in building the nation (positive stage). Although different in approach, the two songs have similarities in fostering a sense of love for the homeland and collective solidarity as the foundation of nationalism. This article recommends that the values ​​of nationalism in these songs are not only a tool for political struggle, but also a means of moral and social education for the community, as reflected in the framework of Comte's Positivism which emphasizes the importance of science and social solidarity in the formation of collective identity. This finding contributes to showing that Yalal Wathon emphasizes the emotional-religious aspect (theological stage), while Sang Surya emphasizes scientific rationality and optimism in building the nation (positive stage). Although different in approach, both songs have similarities in fostering a sense of love for the homeland and collective solidarity as the foundation of nationalism. the use of Positivism theory in cultural studies, which allows similar studies that combine art, philosophy, and history in an analytical framework. Overall, this study successfully combines the emotional and rational aspects of nationalism, and shows its relevance for education and the process of forming the nation's collective identity.